2017
DOI: 10.1002/2016gb005586
|View full text |Cite
|
Sign up to set email alerts
|

A reevaluation of the magnitude and impacts of anthropogenic atmospheric nitrogen inputs on the ocean

Abstract: We report a new synthesis of best estimates of the inputs of fixed nitrogen to the world ocean via atmospheric deposition and compare this to fluvial inputs and dinitrogen fixation. We evaluate the scale of human perturbation of these fluxes. Fluvial inputs dominate inputs to the continental shelf, and we estimate that about 75% of this fluvial nitrogen escapes from the shelf to the open ocean. Biological dinitrogen fixation is the main external source of nitrogen to the open ocean, i.e., beyond the continenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
204
3
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 200 publications
(221 citation statements)
references
References 126 publications
(328 reference statements)
9
204
3
5
Order By: Relevance
“…Depending on the season, limitation by nitrogen or co-limitation by nitrogen and phosphorus in the eastern Mediterranean has been reported (Yücel, 2013(Yücel, , 2017, and references therein). Based on molar N / P ratios in the atmospheric input (order of magnitude higher than that of Redfield; Markaki et al, 2003Markaki et al, , 2010Koçak et al, 2010) and riverine fluxes (at least 1.8 times larger than that of Redfield; Ludwig et al, 2009;Koçak et al, 2010) it has been suggested that the eastern Mediterranean receives excessive amounts of dissolved inorganic nitrogen and that this unbalanced input may result in even more phosphorus deficiency (Ludwig et al, 2009;Koçak et al, 2010), whilst the atmospheric deposition of reactive nitrogen may cause accumulation of nitrogen in the water column (Jickells et al, 2017). Very little research has focused on the importance of water-soluble organic nitrogen input to marine productivity in the eastern Mediterranean (Mace et al, 2003a;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the season, limitation by nitrogen or co-limitation by nitrogen and phosphorus in the eastern Mediterranean has been reported (Yücel, 2013(Yücel, , 2017, and references therein). Based on molar N / P ratios in the atmospheric input (order of magnitude higher than that of Redfield; Markaki et al, 2003Markaki et al, , 2010Koçak et al, 2010) and riverine fluxes (at least 1.8 times larger than that of Redfield; Ludwig et al, 2009;Koçak et al, 2010) it has been suggested that the eastern Mediterranean receives excessive amounts of dissolved inorganic nitrogen and that this unbalanced input may result in even more phosphorus deficiency (Ludwig et al, 2009;Koçak et al, 2010), whilst the atmospheric deposition of reactive nitrogen may cause accumulation of nitrogen in the water column (Jickells et al, 2017). Very little research has focused on the importance of water-soluble organic nitrogen input to marine productivity in the eastern Mediterranean (Mace et al, 2003a;.…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory experiments performed by Seitzinger and Sanders (1999) demonstrated the production of coastal marine bacteria and phytoplankton, which are stimulated by the addition of water-soluble organic nitrogen, 45-75 % being bioavailable. From the mid-1800s to 2000, as a result of anthropogenic activities, reactive nitrogen and reactive anthropogenic organic nitrogen increased by almost 3-and 5-fold, respectively, leading to a significantly modified global nitrogen cycle (Jickells et al, 2017). This in turn has impacted marine nitrogen biogeochemical cycling (Galloway and Cowling, 2002;Galloway et al, 2008;Duce et al, 2008;Jickells et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Dentener et al (2006) the Unites States is found to deviate with inferential dry deposition data. Kanakidou et al (2016) used the ACCMIP simulation results under historical, RCP6.0 and RCP 8.5 emission scenarios to 90 estimate the changes in N deposition driven by human activity in the past (1850), present (2005) and future (2050).…”
Section: Introductionmentioning
confidence: 89%
“…Elevated S and N deposition are also associated with a host of environmental issues such as acidification and eutrophication of the terrestrial system (Bouwman 60 et al, 2002), loss of ecosystem biodiversity (Bobbink et al, 2010), harming the heterotrophic respiration and disturbing the soil decomposition process (Janssens et al, 2010), although some studies found increasing N deposition could benefit the carbon uptake by land processes (Reay et al, 2008;Holland et al, 1997). Similar to the terrestrial system, over-richness of S and N deposition is also a threat to the aquatic system by acidification (Doney et al, 2007) and 65 eutrophication of the ocean (Bergstrom and Jansson, 2006;Jickells, 2006;Jickells et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation